PENGARUH PERILAKU PIMPINAN TERHADAP AKUNTABILITAS MANAJEMEN PERGURUAN TINGGI KEAGAMAAN ISLAM SE-KOTA METRO LAMPUNG - Muhammad Akmansyah, Norma Fitria, (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2019)
Education management in educational institutions is the process of applying management functions in carrying out education and learning tasks to achieve the educational goals. Management theory as something that is relevant to that educational institutions is a consideration. The educational institutions are not managed arbitrarily, which ignores the expectations of the community or stakeholders. University management must be interpreted not only as the distribution of authority and management legality, where every component in the higher education institution must have synergy in science, a balance between teaching, researching and writing scientific papers. The direction and impact of autonomy is highly dependent on the college management and its academics. The purposes of this study are to find out the influence of leadership behavior toward the accountability of the Islamic universities management in Metro City. This research uses a quantitative approach. The data collecting technique used is the multi stage random sampling method. Based on the findings, the study concluded that: leadership behavior has a positive influence on the accountability of the Islamic universities management in Metro City. The test results show that the tcount value is 2.002, and this value is greater than ttable at the 5% significance level of 1.67. It means that the higher the leadership behavior will result higher accountability. This happens because when the leader has strong leadership behavior, it will automatically affect the accountability